Numerical evaluation for SLAP type II tear in shoulder abduction applying the finite element method - Suarez-Hernandez, Maria de la Luz; Urriolagoitia-Sosa, Guillermo; Romero-Ángeles, Beatriz; Carrasco-Hernández, Francisco; Martínez-Reyes, Jacobo; Gallegos-Funes, Francisco Javier; Velázquez-Lozada, Erick; Correa-Corona, Martin Ivan; German-Carcaño, Jesus Manuel; Urriolagoitia-Calderón, Guillermo Manuel (Frontiers in Mechanical Engineering, 2025)
The shoulder joint in the human body is a complex anatomical structure composed of diverse biological tissues that connect and stabilize the joint. This complexity allows the shoulder to perform a wide range of movements and develop specific skills compared to other joints. However, activities such as heavy lifting, forceful jerks of the arm, rapid or aggressive movements of the arm above the shoulder, or sports activities involving repetitive motions can lead to a shoulder labral tear. This injury, known as superior labrum anterior to posterior (SLAP) type II tear, damages the joint, weakens its stability, and limits its motion. The tear diagnosis is based on physical examination tests such as the O'Brien test, the Jobe relocation test, or the internal impingement sign. This research evaluated the shoulder joint from a biomechanical perspective by applying the finite element method to a virtual complex shoulder joint biomodel and analyzing the main elements of the joint, including the bones (cortical and cancellous), ligaments (labrum and joint capsule), and articular cartilage. The main objective was to analyze the effects of loading on the labrum and joint capsule tissues by applying an external load on the humerus, simulating the shoulder abduction movement, and obtaining stress and von Mises stress results. A case study of a healthy shoulder joint structure is developed for comparison. Subsequently, a biomodel modification is proposed to virtually represent the SLAP type II tear in the labral tissue, allowing for numerical analysis of the three-dimensional biomodel. This study investigated the regions of the labrum and capsule most susceptible to tears in the presence of a SLAP type II tear. The labrum does not effectively deepen the socket of the humeral head in the glenoid cavity, resulting in increased mobility of the humeral head. The simulation result is shown to align with observations noted in clinical practice.